BUNG KARNO’s POLITICAL THOUGHT ACCORDING TO PANCASILA: A Study of Bung Karno’s Speech on June 1, 1945, and the President Soekarno/Bung Karno’s Pancasila Course Throughout 1958-1959 - Razuni, Ganjar (JWP (Jurnal Wacana Politik), 2023)
This paper examines the evolution of Bung Karno’s Pancasila concept, tracing its origins from his pivotal June 1, 1945 speech and the comprehensive elucidation of Pancasila during the 1958 Pancasila Course, a crucial moment in shaping its official formulation. Pancasila has become an enduring cornerstone of Indonesian ideology. This prompts a closer examination of Sukarno’s political ideals. This study scrutinizes Bung Karno’s Pancasila ideology within the context of his political philosophy. Methodologically, this article employs a Qualitative-Descriptive approach, primarily drawing on literature and documentary sources. The concept of deconstruction has also used in this article. The findings underscore how Sukarno’s political convictions found expression in Pancasila. His political thought was deeply influenced by Indonesia’s social and political landscape, emphasizing the nation’s diverse yet interconnected destiny and history. Sukarno ingeniously infused this diversity with spiritual unity, encapsulated in the five principles known as “Pancasila.” For Sukarno, Pancasila wasn’t theoretical; it was his practical political tool to manage diversity and avert polarization among Indonesian citizens. The first principle, “Believe in One Supreme God,” was particularly pivotal, serving as the foundation on which the others relied to maintain their integrity. This study sheds light on how Pancasila became more than just a concept; it was Sukarno’s practical response to the complexities of Indonesia’s socio-political landscape, emphasizing unity amidst diversity.